The financial analysis of nitrogen fertilizers and planting systems and its implications on maize agribusiness: Evidence from Peshawar, Pakistan - Farhan Ahmad; Ristina Siti Sundari; Junaid Ahmad; Adnan Arshad (Publisher of Widyagama University of Malang (UWG Press), 2021)
Maize is one of the staple foods that supply the world's food demand. The research aims to determine financial analysis of nitrogen fertilizers and planting systems and its implications on maize agribusiness. The research was conducted in experimental design with a split-plot arrangement comprising four replications. Maize plant density as a system treatment was allocated to main plots (65,000; 75,000; and 85,000 plant per ha). Integrated nitrogen was assigned to sub-plots: control; 0% yard manure (YM) + 100% urea; 100% YM + 0% urea; 50% YM + 50% urea; 75% YM + 25% urea; and 25% YM + 75% urea. Data were recorded on plant harvest, harvest index, and R/C ratio. The result showed that integrated N of 50% Farm Yard Manure + 50% urea in 85,000 plant per ha resulted in a higher harvest index of 31.5% and the highest R/C ratio of 6.2 and enhanced yield of 4,219 kg per ha. This yield almost meets the government's expectations. Total cost was 36,961 PKR, total income was 227,941 PKR, and economic net return reached 190,980 PKR. The government can support the maize crops farmers to activate decomposition household's waste to be organic fertilizer in their house and provide the place for decomposition activity in the crops field to fulfill production government target, food security, and environmental health.JEL Classification: Q01; Q12; Q18